Pathogenesis of vaginal prolapse with the formation of rectocele: a review - Viktor E. Radzinsky; Mekan R. Orazov; Liudmila M. Mikhaleva; Mikhail V. Krestinin; Milana S. Lologaeva (IP Berlin A.V., 2021)
To carry out a systematic analysis of the data available in the modern literature on the pathogenesis of the formation of vaginal prolapse with the formation of rectocele rectum. The failure of the pelvic floor, namely its posterior compartment with the formation of a rectocele against the background of the lowering of the posterior vaginal wall, continues to be one of the most common gynecological diseases. This article presents an analysis of current literature data on the pathogenesis of pelvic organ prolapse with the formation of rectocele. Analyzing the above-mentioned data, it can be noted that the research data of recent years have significantly expanded the understanding of the etiology and pathogenesis of pelvic organ prolapse in its posterior compartment. However, the issues of etiology and pathogenesis of genital prolapse in patients of reproductive age, the role of individual risk factors and their combinations, pathogenetic mechanisms of development are still far from being resolved. Unfortunately, none of the above theories fully explains all the reasons for the formation of pelvic organ prolapse in its posterior compartment.